1994
DOI: 10.1200/jco.1994.12.10.2022
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of high-dose and standard-dose etoposide and cisplatin chemotherapy in patients with extensive-stage small-cell lung cancer.

Abstract: No therapeutic benefits resulted from increasing planned doses by 67% for the first two cycles of EP in patients with extensive-stage SCLC. Higher doses were associated with substantially worse toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(65 citation statements)
references
References 0 publications
1
62
0
2
Order By: Relevance
“…Among the active drugs in SCLC, cyclophosphamide-adriamycin-vincristine (Fukuoka et al, 1986; Feld et al, 1989) or cyclophosphamide-adriamycin-etoposide combinations have long been known as having a good efficacy/toxicity ratio. Other combination chemotherapies such as cisplatin and etoposide have been tested successfully and have given encouraging results in terms of both response and survival rates (Ihde et al, 1984;Maksymiuk et al, 1994; Evans et al, 1985). It rapidly appeared that response to chemotherapy is one of the most important factors for SCLC patients to achieve long-term survival (Osterlind et al, 1986) in association with other known favourable prognostic factors, namely limited disease, good performance status, lower age group, low serum lactate dehydrogenase, low alkaline phosphatases and normal serum sodium and bicarbonate (Cerny et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the active drugs in SCLC, cyclophosphamide-adriamycin-vincristine (Fukuoka et al, 1986; Feld et al, 1989) or cyclophosphamide-adriamycin-etoposide combinations have long been known as having a good efficacy/toxicity ratio. Other combination chemotherapies such as cisplatin and etoposide have been tested successfully and have given encouraging results in terms of both response and survival rates (Ihde et al, 1984;Maksymiuk et al, 1994; Evans et al, 1985). It rapidly appeared that response to chemotherapy is one of the most important factors for SCLC patients to achieve long-term survival (Osterlind et al, 1986) in association with other known favourable prognostic factors, namely limited disease, good performance status, lower age group, low serum lactate dehydrogenase, low alkaline phosphatases and normal serum sodium and bicarbonate (Cerny et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Various drug combinations have been used in sequential chemotherapies in order to improve both response rate and survival. Among these combinations, cisplatin and etoposide (Ihde et al, 1984;Maksymiuk et al, 1994;Evans et al, 1985) or cyclophosphamide, doxorubicin and vincritine (Feld et al, 1989) are two widely applied regimens inducing a 80-90% overall response rate including a 30-40% complete response rate. Despite the high chemosensitivity of SCLC, the 2-and 5-year survivals are low due to the frequent occurrence of chemoresistant relapses after these classical regimens.…”
mentioning
confidence: 99%
“…1,[15][16][17][18][19] To administer this three-drug combination safely, doses of all three drugs were reduced compared with the doses feasible in various two-drug combinations. Even with the routine use of granulocyte-colony stimulating factor (G-CSF), our previous Phase I trial demonstrated that dose-limiting thrombocytopenia prevented meaningful dose escalation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have failed to demonstrate any major improvement in median survival [52][53][54]. However, a recent study in limited SCLC demonstrated that a 20% higher initial dosage of cyclophosphamide and cisplatin achieved a 25% increase in complete remission rate, a 50% increase in the duration of complete remission and a better 2 year survival rate (p=0.016) [42].…”
Section: Intensification Of Chemotherapy With Csfsmentioning
confidence: 99%